Parameters Affecting Resin-Anchored Cable Bolt Performance: Results Of In Situ Evaluations - Joseph C. Zelanko (International Conference on Ground Control in Mining, 1995)
Cable bolt support techniques. including hardware and anchorage systems, continue to evolve to meet U.S. mining requirements. For cable support systems to be successfully implemented into new ground control areas, the mechanics of this support and the potential range of performance need to be better understood. To contribute to this understanding, a series of 36 pull tests were performed on 10 ft long cable bolts using various combinations of hole diameters, resin formulations, anchor types, and with and without resin dams. These tests provided insight as to the influence of these four parameters on cable system performance. Performance was assessed in terms of support capacity (maximum load attained in a pull test), system stiffness (assessed from two intervals of load-deformation), and from the general load-deformation response. Three characteristic load-deformation responses were observed. An Analysis of Variance identified a number of main effects and interactions of significance to support capacity and stiffness. The factorial experiment performed in this study provides insight to the effects of several design parameters associated with resin-anchored cable bolts.